Pelatihan Penyusunan Modul Pra Matematika (MOPRAMAT) dalam Mengenalkan Konsep Matematika Anak Usia Dini - Jumadi, Jumadi; Kristiana, Dian; Azam, Muhammad (Yayasan Arrahman Nahdlatul Wathan, 2025)
Aisyiyah Sukosari Babadan Ponorogo is a school located on the northern edge of the city of Ponorogo which has 2 groups, namely group A aged 4-5 years and group B aged 5-6 years with a total of 3 teachers. With a total of 3 teachers with a Bachelor of Education background. The large number of schools in the Sukosari area means that there are not too many students at this school. Based on the results of interviews with school principals, basic mathematics skills are still low. There are still many students who do not understand the concept of numbers correctly, they are only able to count. The learning carried out by teachers is also not innovative and creative. Early childhood teachers need assistance, workshops for preparing learning modules that are innovative, fun and easy to understand for young children to facilitate a good teaching and learning process. The solutions implemented to solve the problem include: visiting partner schools to map partner problems, compiling modules that are easy to understand according to partner problems, holding training in preparing Mopramat (Pre-Mathematics Module) to introduce early childhood mathematics concepts.